Pathogenicity of Hantaan Virus in Newborn Mice: Genetic Reassortant Study Demonstrating that a Single Amino Acid Change in Glycoprotein G1 Is Related to Virulence - Ebihara, Hideki (American Society for Microbiology, 2000)
Two Hantaan virus strains, clone 1 (cl-1), which is virulent in newborn mice, and its attenuated mutant (mu11E10), were used to examine the pathogenesis of Hantaan virus infection in a mouse model and identify virus factors relating to virulence. After subcutaneous inoculation of newborn BALB/c mice, cl-1 caused fatal disease with high viral multiplication in peripheral organs, but mu11E10 produced nonfatal infection with a low level of virus multiplication. Intracerebral inoculation of either strain caused fatal disease. Histopathological changes in the dead animals were prominent in the brain, indicating that the brain is the target organ and produces the fatal outcome. These results indicate that mu11E10 has a generally less virulent phenotype, and because of decreased multiplication in peripheral tissues, neuroinvasiveness is also decreased. An experiment with genetic reassortant viruses showed that in newborn mice the M segment is the most related to virulence and the L segment is partly related. Sequence comparison detected a single deduced amino acid change (cl-1 Ile to mu11E10 Thr) at amino acid number 515 in glycoprotein G1. One nucleotide change, but no amino acid substitution, was observed in the noncoding region of the L segment. In mouse brain microvascular endothelial cells in vitro, viruses possessing a cl-1-derived M segment grew more rapidly than viruses containing a mu11E10-derived M segment. These results suggest that the single amino acid change in the glycoprotein alters peripheral growth, which affects invasion of the central nervous system in mice.